Determinants of quality of life among Malaysian cancer patients: cross-sectional study - Akhtari-Zavare, Mehrnoosh; Mohd Sidik, Sherina; Periasamy, Ummavathy; Gyanchand Rampal, Lekhraj Rampal; Ismail, Siti Irma Fadhilah; Mahmud, Rozi (BioMed Central, 2018)
Background: Cancer is a serious public health problem not only in Malaysia, also worldwide. The aim of this study was to determine the determinants of quality of life (QOL) among cancer patients in Peninsular Malaysia. Methods: A cross sectional study was conducted among 2120 cancer patients in Peninsular Malaysia, between April 2016 to January 2017. All cancer patients aged 18 years old and above, Malaysian citizens and undergoing cancer treatment at government hospitals were approached to participate in this study and requested to complete a set of validated questionnaires. Inferential statistical tests such as t-test and one-way ANOVA were used to determine the differences between demographic variables, physical effects, clinical factors, psychological effects and self-esteem with the quality of life of cancer patients. Predictor(s) of quality of life were determined by using Multivariate linear regression models. Result: A total 1620 out of 2120 cancer patients participated in this study, giving a response rate of 92%. The majority of cancer patients were female 922 (56.9%), Malays 1031 (63.6%), Muslim 1031 (63.6%), received chemotherapy treatment 1483 (91.5%). Overall, 1138 (70.2%) of the patients had depression and 1500 (92.6%) had anxiety. Statistically significant associations were found between QOL and clinical factors, physical side effects of cancer, psychological effects and self-esteem (p < 0.05). However, among socio-demographics only age, race, religion, working status were significantly associated with QOL. Based on the multivariate regression analysis, the main predictors of QOL among cancer patients in Malaysia were age, self-esteem as positive predictors, and Indian race, nausea, fatigue, hair loss, bleeding as negative predictors. Conclusion: The findings of this study provide a scientific basis to develop a comprehensive program for improving quality of life of cancer patients in Malaysia.